HUBUNGAN BEBAN KERJA DENGAN PELAKSANAAN KOMUNIKASI INTERPERSONAL PERAWAT IGD DAN ICU - Atiek Murharyati; Yustian Hario Fauzi; Ernawati Ernawati; Arista Apriani; Erlina Windyastuti (Universitas Kusuma Husada Surakarta, 2023)
Nurse is a profession that has responsibility for the condition of patients and provides nursing services independently or in groups in the health sector, this can cause a workload. Workload is something that arises from the interaction between the demands of tasks and the work environment. The negative impact of the workload is the nurse's communication with other people. Communication is an important aspect that must be owned by nurses in carrying out nursing care. The purpose of this study is to determine the relationship between workload and the implementation of interpersonal communication between IGD and ICU nurses. This study uses an analytic observational design with a cross sectional approach. This research is conducted on 44 respondents selected using a non-probability sampling total sampling design. Spearmen rank test data analysis test to determine the relationship between workload and the implementation of interpersonal communication between IGD and ICU nurses. The results of the spearmen rank test show that there is a moderate degree of correlation and forms a negative relationship between workload and interpersonal communication. The results show that the P Value is 0.003 (<0.05) with a correlation value of -0.433. This shows that the higher the workload the less interpersonal communication is done. For further researchers, it is possible to involve patients as respondents in research so that they can strengthen the results of the interpersonal communication questionnaire.